Processes in third language acquisition - Hammarberg, Björn, 1935- (Edinburgh University Press, 2009)
This volume brings together six case studies of an adult multilingual speaker who acquires a new language through social interaction. The book deals especially with the multilingual situation, the learner's acquisitional activities, and the involvement of background languages in the process of speaking. It offers a coherent study of various linguistic phenomena in one individual, including patterns and functions of language switching, word search in interaction, hypothetical construction of words, and articulatory settings in speaking. The main languages involved are English (L1), German (L2) and Swedish (L3). The activation of these languages in the learner's speech is examined in a cognitive perspective in relation to current models of the speaking process. A longitudinal corpus of NNS-NS conversations covering 21 months from the beginner stage provides the main data for these studies. Key Features Presents an example of an active and purposeful language acquirer Explores cross-linguistic influence in a multilingual setting Highlights the significance of prior L2 knowledge in L3 performance Useful for students and researchers interested in second and third language acquisition, individual multilingualism and the human speaking process.